Organizational diversity learning framework: Going beyond diversity training programs - Fujimoto, Yuka *; Hartel, Charmine E. J. (Emerald, 2017)
To overcome the shortcomings of diversity training programs, this paper conceptualizes an organizational diversity-learning framework, which features an organizational structural intervention for employees’ joint decision-making process with other employees from different statuses and roles. By integrating diversity learning, deliberative democracy theories, and organizational diversity integration and learning perspectives, we make a theoretical and practical contribution to employees’ behavioral, cognitive, and attitudinal diversity in learning to work more effectively with different employees. We conclude with directions for future research.